(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
To find out preferred cucurbit host(s) of the pumpkin beetle and to determine the susceptibility of ten different cucurbits to the pest, a trial was conducted under field conditions. The results revealed that the most preferred host of the red pumpkin beetle (RPB) was muskmelon, which was followed by khira, cucumber and sweet gourd, and these may be graded as susceptible hosts. Bitter gourd, sponge gourd, ribbed gourd and snake gourd were least or non preferred hosts of RPB and these may be graded as resistant hosts. Other two crops, the bottle gourd and ash gourd were moderately preferred hosts of the insect and these may be graded as moderately susceptible hosts. The order of the most preferred host of the blue pumpkin beetle may be shown as bitter gourd> ribbed gourd> sponge gourd. Of these cucurbits, population of blue pumpkin beetle was much higher than that of red pumpkin beetle. The hosts most preferred to RPB are less preferred or not preferred to the blue pumpkin beetle. The field trials revealed that the order of preference of RPB for ten tested cucurbit hosts was muskmelon> sweet gourd> cucumber > khira > ash gourd > bottle gourd > sponge gourd ? ribbed gourd ? snake gourd > bitter gourd. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15322 J. Asiat. Soc. Bangladesh, Sci. 38(1): 75-82, June 2012